Long-Term Behaviour of Model Piers in Weak Rock - Chae, Kyu-Jong (My University, 1984)
The research contained in this thesis is concerned with longterm behaviour of drilled piers socketed in weak rock. The experimental work involved testing of two steel and seven concrete model piers. The 25.4 mm (1.0 in) diameter steel piers had relatively smooth socket walls (RF = 0.033) and were socketed into pseudo-rock material. The concrete piers were 76.2 mm (3.0 in) in diameter and were socketed into weak rock (Queenston Shale). The concrete piers were of two types: conventional socketed piers with relatively smooth socket walls (RF = 0.025) and grooved piers with relatively rough socket walls (RF = 0.081 and 0.303).
The piers were tested under two condition of load support, shaft resistance only and combined shaft resistance and end-bearing support conditions.
In case of steel piers, electrical resistance strain gauges were mounted on the pier shaft to measure the load distribution along the shaft of the piers. For concrete piers under combined shaft resistance and end-bearing support conditions, flat jack load cells with Marsh and Budenberg pressure gauges and/or electrical pressure transducers were used to measure the load transfer at the base.
All model piers were axially loaded in the laboratory using load frames designed and fabricated for this purpose. The axial loads were iii applied by the air cylinders and held constant throughout the period of testing using a regulated air pressure supply.
The test results confirmed that performance of socketed piers can be significantly improved by increasing the roughness of the pier-rock interface. Both the primary creep rate and the load transfer with time were larger for piers with small shaft roughness.
A second stage of creep having a much lower creep rate was observed for all model tests. The time to the end of primary creep was found to depend on the roughness of the socket wall. The primary and secondary creep rate appeared to be dependent on the stress level, shaft roughness, compressive strength of weak rock and support conditions.
The results of the model tests are compared with available test data and with values predicted using methods based on viscoelastic analysis. This method of analysis for piles in clay soils has been modified for application to socket piers in weak rock. It is suggested that the modifications can be used to estimate the long-term settlement of socket piers in weak rock
Keywords: long term behaviour; drilled piers; weak rock; concrete; Civil and Environmental Engineering; Civil Engineering; Construction Engineering and Management; Engineering; Civil and Environmental Engineering